The Permian Tiaraju bivalve assemblage, Passa Dois Group, southern Brazil: biostratigraphic and paleobiogeographic significance - Marcello Guimarães Simões; Juliana Machado David; Luiz Eduardo Anelli; Carla Klein; Suzana Aparecida Matos; Vitor Bonatto Guerrini; Lucas Veríssimo Warren (Brazilian Journal of Geology)
ABSTRACT: Permian bivalves of the Paraná Basin evolved in a large inland sea, under conditions of extreme isolation and environmental stress. Although known since 1918, its evolutionary history is still obscure due to the incomplete and biased information on faunal composition and stratigraphic distribution of various assemblages. Hence, the description of the Tiaraju assemblage, the only known bivalve occurrence in the Passa Dois Group from the southernmost Brazil, adds new key information on the composition, biocorrelation and age of this unique molluscan fauna. Terraia falconeri, Cowperesia emerita, Holdhausiella elongata, and Terraia altissima were recorded and described. T. falconeri is the commonest species, followed by C. emerita, H. elongata and T. altissima. The faunule is mainly composed by Terrainae, lacking Pinzonellinae. Assemblage is, thus, poorly diversified, both regarding the faunal composition and guild structure (only infaunal, facultatively motile, unattached, suspension feeders present). Cowperesia emerita and T. altissima strongly indicate biocorrelation with assemblages of the Rio do Rasto and Gai-As formations, Brazil and Namibia, providing an age no younger than the mid-Permian (Wordian-Captianian). On the light of this information, the current geological map of the Tiaraju region, São Gabriel, and the local boundary between the Teresina and Rio do Rasto formations requires reevaluation.